The Role of Public Policy Innovation in Accelerating Climate Change Mitigation - Sumarsyah, Wilda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the role of public policy innovation in accelerating climate change mitigation efforts through adaptive and participatory policy approaches. Using systematic literature review methods and comparative policy analysis, the research examines various innovative practices implemented at the national and local levels, such as market-based instruments, green regulations, and multi‐actor collaboration. The results of the analysis show that public policy innovations that integrate low-carbon technologies, economic incentive mechanisms, and collaborative governance are able to strengthen the effectiveness of mitigation strategies, reduce greenhouse gas emissions, and increase environmental resilience. These findings confirm that the success of accelerating climate change mitigation is greatly influenced by the government's capacity to create policies that are flexible, data-driven, and oriented towards long-term sustainability. The study makes a theoretical contribution by broadening the understanding of the relationship between policy innovation and climate action, while providing practical recommendations for policymakers to adopt innovative approaches that are responsive to social, economic, and ecological dynamics.